Iatrogenic Ureteral Obstruction During Transvaginal Oocyte Retrieval - Ali Sami Gurbuz (International Brazilian Journal of Urology)
ABSTRACT Transvaginal oocyte retrieval is a crucial step in assisted reproductive technology. Various complications may arise during this procedure. Ureteral injury is a rare, but a serious complication in gynecological practice. During oocyte retrieval, ureteral injuries, detachment and obstruction can be seen, though rare. In this study, we will present ureteral obstruction that develops secondary to small hematoma, which mimics ovarian cyst torsion or ruptured ovarian cyst.